Comprehensive genome analysis of Burkholderia contaminans SK875, a quorum-sensing strain isolated from the swine - Eiseul Kim; Hae-In Jung; Si Hong Park; Hae-Yeong Kim; Soo-Ki Kim (AMB Express, 2023)
Keypoints We first report the genome characteristics of B. contaminans SK875. The B. contaminans SK875 genome carries virulence and quorum sensing-related genes. The SK875 has 186 unique genes, such as toxin higB, betA, and hypothetical proteins